Wellbeing, emotional response and stress among lay responders dispatched to suspected out-of-hospital cardiac arrests. (14th October 2021) - Berglund, E; Olsson, E; Jonsson, M; Svensson, L; Hollenberg, J; Claesson, A; Nordberg, P; Lundgren, P; Hogstedt, A; Ringh, M; ,
Abstract: Introduction: The recent 2021 European Resuscitation Council guidelines strongly advocate systems for smartphone-aided dispatch of lay volunteers to out-of-hospital cardiac arrests (OHCAs) to perform CPR and bring automated external defibrillators. Systems alike have been implemented in nearly half of all the European countries and are emerging in around the world. This study aimed to investigate the emotional responses, post-traumatic stress reactions and levels of wellbeing among smartphone-alerted lay responders dispatched to cases of suspected OHCAs. Methods: Participants rated their emotional responses online, at 90 minutes and at 4–6 weeks after an incident. Level of emotional response was measured in two dimensions: "activation" – from deactivation to activation, and "valence" – from unpleasantness to pleasantness. At 4–6 weeks, WHO wellbeing index and level of post-traumatic stress (PTSD) were also rated. Lay responders were stratified by level of exposure: (Un-exp): unexposed, (Exp-1): tried to reach, and (Exp-2): reached the suspected OHCA. Results: Altogether, 886 (26%) unexposed and 1389 (64%) exposed responders completed the survey. "Activation" was elevated in the exposed groups: Un-exp: 6.7, Exp-1: 7.4 and Exp-2: 7.5, (p<0.001) and "valence" was highest in the Un-exp group: 6.5, vs. Exp-1: 6.3, and Exp-2: 6.1, (p<0.001). Mean scores for PTSD was below clinical cutoff, Un-exp: 10.4, vs. Exp-1: 8.8 and Exp-2: 9.2 (p=0.007). Wellbeing index showed no differences, Un-exp: 77.7, Exp-1: 77.8 and Exp-2: 78.2 (p=0.963). Conclusion: Laypersons responding to smartphone alerts to suspected OHCAs rated the experience as high-energy and mostly positive. No harm to lay responders was seen. The responding groups had low post-traumatic stress scores, and high-level general wellbeing at follow-up. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Region Stockholm